Cervical cancer prevention: association of new techniques of molecular biology with the oncotic cytology in detection of human papillomavirus (HPV) - Bringhenti, Márcia Elena Z.; Dozza, Ticiana G.; Martins, Toni Ricardo; Bazzo, Maria Luiza (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: worldwilde, the cervical cancer is known as one of the most frequent cause of death in female population. Persistent infection with oncogenic human papillomavirus (HPV) is the main risk factor for cervical cancer and its precursor lesions. Objective: to evaluate the diagnostic methods of cervical cancer: oncotic cytology, HPV DNA by PCR, detection of mRNA E6 / E7 proteins of high-risk HPV, to add new markers in the detection of HPV. Methods: were evaluated 3,000 results of oncotic cytology from patients referred to Vital Laboratory, Nonoai- RS, Brazil, from March 2009 to January 2010. The results were grouped according age and Bethesda classification, 2001. Group A included patients with previous altered cytology and Group B patients without abnormalities in cytology. To molecular tests were collected 47 samples, 22 from group A and 25 from group B. Three samples from group B presented PCR inhibitors and were excluded. The detection of HPV was made by polymerase chain reaction (PCR) using the consensus primers MY9/11 and GP5 +/6 +. The mRNA E6 / E7 proteins were detected by real-time NASBA. Results: in samples of group A, DNA/HPV was detected in 14 (64%) samples, and mRNA E6 / E7 proteins of HPV was detected in 6 (27%) samples. All 22 samples of group B were negative to molecular methods. Conclusion: in this study, the previous altered cytology associated with molecular methods indicates the need for monitoring or therapeutic intervention of patients. The oncotic cytology associated with the detection of HPV DNA by PCR and the expression of oncoproteins E6 / E7 are alternatives to identify early lesions in patients with high risk of developing cervical cancer.